2009
DOI: 10.1007/s10620-009-0782-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Nonsynonymous Variants of the IL23R with Familial and Sporadic Inflammatory Bowel Disease in Women

Abstract: We replicated the association of IL23R R381Q with CD but not UC, and we observed an association of L310P with UC, but not CD, in a central Pennsylvania population. Further analysis of the distribution of IL23R variants revealed that these effects were largely female-specific. The results suggest that IL23R R381Q confers protection against CD and that L310P confers protection against UC in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In addition, different races and ethnic groups have different degrees of susceptibility to IBD [5]. A number of studies have shown an association between IBD susceptibility and the nucleotide-binding oligomerization domain 2 gene ( NOD2, also known as CARD15 ), interleukin-23 receptor gene ( IL23r ), organic cation transporter novel type 1 gene ( OCTN1 ), and the intergenic region ( IGR ) variants [6-9]. NOD2 gene mutations have been extensively studied and described in the literature in terms of IBD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different races and ethnic groups have different degrees of susceptibility to IBD [5]. A number of studies have shown an association between IBD susceptibility and the nucleotide-binding oligomerization domain 2 gene ( NOD2, also known as CARD15 ), interleukin-23 receptor gene ( IL23r ), organic cation transporter novel type 1 gene ( OCTN1 ), and the intergenic region ( IGR ) variants [6-9]. NOD2 gene mutations have been extensively studied and described in the literature in terms of IBD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…DNA amount and quality were measured by spectrophotometry. IL23R and ATG16L1 variants genotyping was performed using polymerase chain reaction (PCR) restriction fragment length polymorphism analysis (RFLP) as described respectively by Lin et al and Csöngei et al [10, 14]. …”
Section: Methodsmentioning
confidence: 99%
“…In Ulcerative colitis, the effect of this mutation seems to be insignificant [9]. In addition, Lin Z et al suggested the role of IL23R (L310P) as a protective polymorphism in UC females [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The minor Q381 allele conferred approximately twofold greater protection against psoriasis and ankylosing spondylitis, and threefold protection against Crohn's disease [117]. Analysis from Lin and co-workers indicated a female specific protective effect of R381Q against Crohn's disease [118]. The polymorphism R381Q occurs at a frequency of 0-17% depending on the population [81].…”
Section: Molecular Analysis Of Disease-associated Il-23r Snpsmentioning
confidence: 99%
“…However, Lin and coworkers suggested L310P as a protective polymorphism in UC females. Furthermore, they examined the nsSNP Q3H (rs1884444) of IL23R, also located within exon 7, and observed no association with IBD [118]. heterozygous genotype showed impaired IL-23 induced T H 17 response [117].…”
Section: Molecular Analysis Of Disease-associated Il-23r Snpsmentioning
confidence: 99%